Carers' experiences of timely access to and use of dementia care services in eight European countries. Issue 2 (16th February 2021) - Jelley, Hannah; Kerpershoek, Liselot; Verhey, Frans; Wolfs, Claire; de Vugt, Marjolein; Bieber, Anja; Stephan, Astrid; Meyer, Gabriele; Michelet, Mona; Selbaek, Geir; Sjölund, Britt-Marie; Sköldunger, Anders; et al.
Abstract: Timely access to care services is crucial to support people with dementia and their family carers to live well. Carers of people with dementia (N = 390), recruited from eight countries, completed semi-structured interviews about their experiences of either accessing or not using formal care services over a 12-month period in the Access to Timely Formal Care (Actifcare) study. Participant responses were summarised using content analysis, categorised into clusters and frequencies were calculated. Less than half of the participants (42.3%) reported service use. Of those using services, 72.8 per cent reported timely access and of those not using services 67.2 per cent were satisfied with this situation. However, substantial minorities either reported access at the wrong time (27.2%), or feeling dissatisfied or mixed feelings about not accessing services (32.8%). Reasons for not using services included use not necessary yet, the carer provided support or refusal. Reasons given for using services included changes in the condition of the person with dementia, the service's ability to meet individual needs, not coping or the opportunity to access services arose. Facilitators and barriers to service use included whether participants experienced supportive professionals, the speed of the process, whether the general practitioner was helpful, participant's own proactive attitude and the quality of information received. To achieve timely support, simplified pathways to use of formal care services are needed.